Application of metabolomics profiling in the analysis of metabolites and taste quality in different subtypes of white tea. (April 2018) - Yang, Chen; Hu, Zhengyan; Lu, Meiling; Li, Pengliang; Tan, Junfeng; Chen, Mei; Lv, Haipeng; Zhu, Yin; Zhang, Yue; Guo, Li; Peng, Qunhua; Dai, Weidong; et al.
Abstract: Three subtypes of white tea, Silver Needle (SN), White Peony (WP), and Shou Mei (SM), differ in their taste, aroma, bioactivity, and commercial value. Here, a metabolomics investigation on the chemical compositions combining taste equivalent-quantification and dose-over-threshold (DoT) determination on the taste qualities were applied to comprehensively characterize the white tea subtypes for the first time. Significant differences in the contents of catechins, dimeric catechins, amino acids, phenolic acids, flavonol/flavone glycosides, and aroma precursors were observed among these 3 white teas. Metabolite content comparison and partial least-squares (PLS) analysis suggest that theanine, aspartic acid, asparagine, and AMP were positively correlated with the umami taste in white tea, and flavan-3-ols, theasinensins, procyanidin B3, and theobromine had positive correlations with higher bitterness and astringency tastes. In addition, puckering astringent (-)-epigallocatechin gallate (EGCG), (-)-epicatechin gallate (ECG) and theogallin, bitter-tasting caffeine, and the mouth-drying/velvety-like astringent γ -aminobutyric acid (GABA) were identified as key taste compounds of white tea infusion by absolute quantification and DoT factor calculations. This work provided systematic and comprehensive knowledge on the chemical components, taste qualities, and sensory active metabolites for the subtypes of white tea. Graphical abstract: Highlights: Metabolomics combining taste equivalent-quantification and DoT was applied to white teas. 99 metabolites were identified and compared among the 3 white tea subtypes. Some components were identified as key taste compounds of white tea. Systematic knowledge on chemical compositions and taste qualities of white tea.